Should private companies have the same SECa disclosure requirements as public companies? A debate - Phalippou, L; Brown, G (Wiley, 2022)

(untitled)
As with any important policy decision, the question of mandated disclosure for private equity must weigh the potential benefits against the costs of implementation. At the 2022 Private Equity Research Symposium hosted by Oxford University, Oxford's Ludovic Phalippou and UNC-Chapel Hill's Gregory Brown debated the merits of greater mandated financial reporting for private companies. Phalippou's arguments in favor of more disclosure center on the potential lack of alignment between private equity fund general partners (GPs) and limited partners (LPs), which can distort the incentives of GPs to be transparent and honest with LPs. Brown's arguments against increasing mandated disclosure focus on the potentially large costs associated with substantially more reporting, especially for smaller companies. These costs could change the landscape of private investments in a way that reduces investment in innovative, high-growth companies.